Treatment of air leak in polytrauma patients with blunt chest injury. Issue 9 (September 2017) - Halat, Gabriel; Negrin, Lukas L.; Chrysou, Konstantina; Hoksch, Beatrix; Schmid, Ralph A.; Kocher, Gregor J.
Abstract: Introduction: Precise diagnostics and an adequate therapeutic approach are mandatory in the treatment of air leak in polytrauma patients with blunt chest trauma. The aim of this study was to evaluate the incidence, characteristics, and management of air leak following this injury pattern. Patients and methods: Data from 110 polytrauma patients was collected retrospectively. Fifty-four patients received initial treatment by chest tube placement for pneumothorax. These patients were classified into two groups, one with severe air leak and one with minor air leak. An evaluation of injury pattern, chest wall injuries in particular, duration of air leak, reason for drainage maintenance in place, hospital length of stay, ICU stay, ventilator duration, type of treatment, and the delay to surgical intervention was performed. Results: Whereas 4 patients showed severe air leak and were subsequently scheduled for timely surgical intervention, the remaining 50 patients only showed minor air leak. Only 7 patients with minor air leak suffered from prolonged air leak (>5 days), which spontaneously resolved in all of them after a mean duration of 7.7 days (range 6–12 days). Absence of a prolonged air leak resulted in a shorter length of stay and a shorter duration of mechanical ventilation, although no statistical significance was observed. Conclusions: Early spontaneous cessation of most minor air leaks as well as early surgical intervention for severe air leak lead to very satisfactory patient outcomes with a relatively short hospital stay in our patients. We therefore advocate early surgery for lacerations of the pulmonary parenchyma resulting in severe air leak, whereas minor air leaks can usually be treated conservatively.